The Influence of Service Quality, Product Quality, and Customer Value on Customer Satisfaction and Customer Loyalty in the Menokwari-Sorong Diocese Credit Union, West Papua Province - Ibori, Lewi; Iswati, Sri; Setijaningrum, Erna; Lestari, Yetty Dwi; Supriharyanti, Elisabeth (Migration Letters, 2023)
The purpose of this research is to investigate the impact of Service Quality, Product Quality, and Customer Value on Customer Satisfaction and Customer Value on Customer Satisfaction and Customer Loyalty in the Manokwari-Sorong Diocese Credit Union, West Papua and Southwest Papua Provinces. This research focuses on the corporate banking sector with Credit Unions as the research subject. The data used in this research comes from primary data obtained through the use of questionnaires and other sources. The questionnaire uses a Likert scale with participation from 360 customers. Data analysis in this research was carried out using Structural Equation Modeling (SEM) with the AMOS version 6 program to test hypotheses. In contrast, SPSS 18 software was used to measure construct validity and test data reliability. The research results show service quality has a significant impact on customer satisfaction at the Manokwari-Sorong Diocese Credit Union, West Papua and Southwest Papua Provinces, so hypothesis 1 is accepted. Service quality does not have a significant impact on customer loyalty at the Manokwari-Sorong Diocese Credit Union, West Papua and Southwest Papua Provinces, so hypothesis 2 is rejected. Product quality has a significant effect on customer satisfaction at the Manokwari-Sorong Diocese Credit Union, West Papua and Southwest Papua Provinces, so hypothesis 3 is accepted. Product quality has a significant impact on customer loyalty at the Manokwari-Sorong Diocese Credit Union, West Papua and Southwest Papua Provinces, so hypothesis 4 is accepted. Customer value has a significant effect on customer satisfaction at the Manokwari-Sorong Diocese Credit Union, West Papua and Southwest Papua Provinces, so hypothesis 5 is accepted. Customer value does not have a significant impact on customer loyalty at the Manokwari-Sorong Diocese Credit Union, West Papua Province, so hypothesis 6 is rejected. Customer satisfaction has a significant effect on customer loyalty in the Manokwari-Sorong Diocese Credit Union, West Papua and Southwest Papua Provinces, so hypothesis 7 is accepted.